2022
DOI: 10.3389/fmed.2022.949554
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Interpretation of SARS-CoV-2 Antigen Detection by Immunochromatography

Abstract: SARS-CoV-2 is a serious infectious respiratory virus that can cause lung, heart, kidney, and liver damage and even cause death. Early diagnosis of SARS-CoV-2 infection is vital for epidemic prevention and control. At present, the gold standard of COVID-19 diagnosis is nucleic acid detection of SARS-CoV-2. However, the nucleic acid detection of SARS-CoV-2 requires high site requirements and technology requirements, and the detection is time-consuming and cannot fully meet clinical needs. Although SARS-CoV-2 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Shao concluded that while SARS-CoV-2 antigen test findings cannot be utilized to diagnose COVID-19 directly, they may be used for early triage and immediate care of questionable groups. SARS-CoV-2 antigen testing is susceptible to false-positive and false-negative findings due to technical limitations ( 36 ). According to Fournier et al, antigen testing is unsatisfactory due to its lack of sensitivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shao concluded that while SARS-CoV-2 antigen test findings cannot be utilized to diagnose COVID-19 directly, they may be used for early triage and immediate care of questionable groups. SARS-CoV-2 antigen testing is susceptible to false-positive and false-negative findings due to technical limitations ( 36 ). According to Fournier et al, antigen testing is unsatisfactory due to its lack of sensitivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Later, the rapid diagnosis of SARS-CoV-2 antigen has played a more and more important role in epidemic prevention [ 4 , 5 ]. Colloidal gold immunochromatographic assay (GICA)-based SARS-CoV-2 antigen testing kits are mainly developed, which has the advantages in terms of low cost, rapid detection and self-service to meet the needs of virus screening [ 6 ]. However, GICA is not sensitive enough to detect low abundance samples of early infection, thus limiting its contribution to epidemic prevention [ [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 is the cause of the current coronavirus pandemic, which can lead to serious health consequences such as lung damage, heart complications, and even death. 1 It has spread at an alarming rate due to its highly contagious nature and wide range of transmission pathways, resulting in more than 766.44 million people being infected worldwide, with over 6.93 million fatalities (as of May 2023). 2 This pandemic has become more difficult to contain with the emergence of mutant strains.…”
Section: Introductionmentioning
confidence: 99%
“…2 This pandemic has become more difficult to contain with the emergence of mutant strains. 1 To reduce the spread of the virus, the early identification and diagnosis of patients is essential, hence there is a need for simple, convenient, and rapid, yet accurate assays to detect SARS-CoV-2. 4,5…”
Section: Introductionmentioning
confidence: 99%